(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions defined between an ideal topological space and a bitopological space, namely upper almost τ^(σ_1,σ_2)-continuous multifunctions and lower almost τ^(σ_1,σ_2)-continuous multifunctions. Moreover, several characterizations and some properties concerning upper almost τ^(σ_1,σ_2)-continuous multifunctions and lower almost τ^(σ_1,σ_2)-continuous multifunctions are considered. Furthermore, the relationships between τ^(σ_1,σ_2)-continuity and almost τ^(σ_1,σ_2)-continuity are discussed.